From Paganism to Christianity. General Remarks on the Religious Changes in Petra (1st–6th Cent. AD) - Al-Nasarat, Mohammed (Studia Ceranea, 2018)
The aim of this paper is to shed some light on the period of Petra’s passage from paganism to Christianity, which saw the deterioration of pagan beliefs and the struggle for survival between paganism and Christianity. The recognition of Christianity as the official religion of the Byzantine Empire in 313 AD did not mean that paganism had disappeared from Petra. In fact, most of the Nabataean temples in the city remained open until the second half of the 4th century AD, when the city was hit by the earthquake of 363. It was this event that had the greatest impact on the abandoning of the city’s temples, such as the Temple of the Winged Lions, the Temple of Qasr el-Bent and the Great Temple. The historical and archaeological evidence confirms the construction of a numer of churches in Petra, which received considerable attention from the Christian clergy and the administration of the city during the 5th and 6th centuries AD.